Therapeutic Potentials of Colocasia affinis Leaf Extract for the Alleviation of Streptozotocin-Induced Diabetes and Diabetic Complications: In vivo and in silico-Based Studies - Shill MC; Bepari AK; Khan M; Tasneem Z; Ahmed T; Hasan MA; Alam MJ; Hossain M; Rahman MA; Sharker SM; Shahriar M; Rahman GMS; et al. (Dove Medical Press, 2021)
Manik Chandra Shill,1 Asim Kumar Bepari,1 Mahi Khan,1 Zarin Tasneem,1 Tania Ahmed,1 Md Asif Hasan,1 Md Jahir Alam,1 Murad Hossain,1 Md Ashrafur Rahman,1 Shazid Md Sharker,1 Masum Shahriar,2 Ghazi Muhammad Sayedur Rahman,1 Hasan Mahmud Reza1 1Department of Pharmaceutical Sciences, North South University, Bashundhara, Dhaka, 1229, Bangladesh; 2Department of Pharmacy, Jahangirnagar University, Savar, BangladeshCorrespondence: Manik Chandra Shill; Hasan Mahmud RezaDepartment of Pharmaceutical Sciences, North South University, Bashundhara, Dhaka, 1229, BangladeshEmail manik.shill@northsouth.edu; hasan.reza@northsouth.eduIntroduction: Hypoglycemia in diabetes mellitus (DM) correlates with hepatic impairment, nephropathy, lipid abnormalities, and oxidative stress and subsequently complicates the disease pathogenesis. Medicinal plants have been used for the management of diabetes since ancient times. In this study, we explored the potentials of Colocasia affinis (CA), a plant known to possess anti-allergic and anti-inflammatory activities, as a remedy for diabetes and related complications.Methods: We induced diabetes in rats using a single intraperitoneal dose (65 mg/kg) of streptozotocin (STZ). We next treated the rats with an ethanolic extract of leaves of CA to reveal its antidiabetic and organ-protective potentials. Biomarkers of diabetes, inflammation, and oxidative stress were measured using biochemical and histopathological analysis. We also performed molecular docking for three major phytochemicals (kaempferol, myricetin, and rosmarinic acid) of CA.Results: Oral administration of the CA leaves extract at 250 mg/kg and 500 mg/kg doses decreased blood glucose level significantly (p< 0.05) in STZ-induced diabetic rats. The extract also considerably attenuated plasma HbA1c levels and normalized blood lipids, glycogen, alanine aminotransferase (ALT), and aspartate aminotransferase (AST). Additionally, treatment with the extract improved kidney complications by decreasing serum creatinine and blood urea nitrogen (BUN) levels. Furthermore, CA leaves extract normalized nitric oxide (NO) and advance oxidative protein products (AOPP) in diabetic rats. The extract also showed significant improvement of the antioxidant enzymes glutathione dismutase (GSH) and superoxide dismutase (SOD) at a dose of 500 mg/kg. Besides, histological investigation demonstrated attenuation of inflammation of the vital organs, including the liver and the kidney. In silico studies revealed that three major phytochemicals (kaempferol, myricetin, and rosmarinic acid) of the ethanolic extract of leaves of CA can inhibit several molecular targets of diabetes and inflammation.Conclusion: Collectively, our results demonstrated the therapeutic potentials of CA for the mitigation of diabetes and diabetic complications.Keywords: diabetes mellitus, Colocasia affinis, antidiabetic potentials, vital organs protection, oxidative stress markers